2005
DOI: 10.1021/ja055288c
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Mechanism of Palladium-Catalyzed Allylic Amination

Abstract: A comparative investigation into palladium-catalyzed allylic amination of unsubstituted aziridines and secondary amines has been carried out. The use of NH aziridines as nucleophiles favors formation of valuable branched products in the case of aliphatic allyl acetates. The regioselectivity of this reaction is opposite to that observed when other amines are used as nucleophiles. Our study provides evidence for the palladium-catalyzed isomerization of the branched (kinetic) product formed with common secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
67
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(70 citation statements)
references
References 58 publications
3
67
0
Order By: Relevance
“…Like the published reactions of aziridines, the regioselectivities of the reactions in Table 3 were independent of the reaction time. [4] By comparison, these reactions with morpholine formed the opposite regioisomeric products that result from substitution at the less hindered position of the allyl intermediate, just as reported with related bisphosphine ligands. [4] Reactions with cinnamyl carbonate catalyzed by [{Pd(h 3 -allyl)Cl} 2 ] and xantphos in dichloromethane also formed the linear product.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…Like the published reactions of aziridines, the regioselectivities of the reactions in Table 3 were independent of the reaction time. [4] By comparison, these reactions with morpholine formed the opposite regioisomeric products that result from substitution at the less hindered position of the allyl intermediate, just as reported with related bisphosphine ligands. [4] Reactions with cinnamyl carbonate catalyzed by [{Pd(h 3 -allyl)Cl} 2 ] and xantphos in dichloromethane also formed the linear product.…”
supporting
confidence: 52%
“…[3,4] During studies to develop the scope of the hydroamination of dienes, [5][6][7] we found that the reactions of hydrazine and hydroxylamine derivatives occur irreversibly at the more substituted position of both prenyl and crotyl palladium intermediates. We explored this transformation further because, unlike the products from additions of aziridines, [3,4] the products from addition of hydrazine and hydroxylamine derivatives could be readily transformed into primary tertalkylamines or sec-alkylamines. The synthesis of primary amines containing tertiary alkyl groups is challenging because many of the conventional methods, such as nucleophilic substitution and additions to imines, are difficult to conduct at tertiary electrophiles and at ketimines, [8,9] and few catalytic reactions have been developed that form tert-alkyl-substituted amines.…”
mentioning
confidence: 99%
“…Like the published reactions of aziridines, the regioselectivities of the reactions in Table 3 were independent of the reaction time. [4] By comparison, these reactions with morpholine formed the opposite regioisomeric products that result from substitution at the less hindered position of the allyl intermediate, just as reported with related bisphosphine ligands. [4] Reactions with cinnamyl carbonate catalyzed by [{Pd(η 3 -allyl)Cl} 2 ] and xantphos in dichloromethane also formed the linear product.…”
supporting
confidence: 52%
“…[3,4] During studies to develop the scope of the hydroamination of dienes, [5][6][7] we found that the reactions of hydrazine and hydroxylamine derivatives occur irreversibly at the more substituted position of both prenyl and crotyl palladium intermediates. We explored this transformation further because, unlike the products from additions of aziridines, [3,4] the products from addition of hydrazine and hydroxylamine derivatives could be readily transformed into primary tert-alkylamines or sec-alkylamines. The synthesis of primary amines containing tertiary alkyl groups is challenging because many of the conventional methods, such as nucleophilic substitution and additions to imines, are difficult to conduct at tertiary electrophiles and at ketimines, [8,9] and few catalytic reactions have been developed that form tert-alkylsubstituted amines.…”
Section: Abstract Allylic Substitution; Homogeneous Catalysis; Hydroamentioning
confidence: 99%
“…The same amines can be obtained via the allylic amination of the corresponding acetates. [35][36][37][38] Nevertheless, the direct hydroamination of myrcene is proven to be the better route because the acetates are rarely available. If the pathway is telomerisation, the so-called tail-to-tail telomer (tttelomer, 3) is mainly generated.…”
Section: Hydroamination Under Single Phase Conditionsmentioning
confidence: 99%